1984
DOI: 10.1002/food.19840280308
|View full text |Cite
|
Sign up to set email alerts
|

Thermoreversible Gele auf Polysaccharidbasis (Übersichtsartikel)

Abstract: Nach einem Überblick über physikochemisches Verhalten, Strukturbildung und Charakterisierung thermoreversibler Polysaccharidgele werden, gegliedert nach den Stoffklassen der „Polygalactane”︁ und der „Polyglucane”︁, die einzelnen Stoffsysteme unter Betonung struktureller Aspekte besprochen. Im Vordergrund stehen dabei gelbildende Polysaccharide aus Rot‐ und Braunalgen; daneben werden gelbildende Maltodextrine und Cellulosesulfate behandelt. Abschließend wird auf einige Zusammenhänge zwischen chemischer Struktur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 88 publications
1
2
0
Order By: Relevance
“…Haswell was not able to homologize it with any structure found in any other animal. The present study shows that it is homologous with the archenteron of other animals, as had been suggested by Dawydoff (1928). The evidence for this conclusion is as follows :-The endoccele arises in that layer which produces both the reproductive organs and excretory cells.…”
Section: : D \ Va'supporting
confidence: 87%
“…Haswell was not able to homologize it with any structure found in any other animal. The present study shows that it is homologous with the archenteron of other animals, as had been suggested by Dawydoff (1928). The evidence for this conclusion is as follows :-The endoccele arises in that layer which produces both the reproductive organs and excretory cells.…”
Section: : D \ Va'supporting
confidence: 87%
“…The picture sketched above somewhat resembles formation of thermoreversible gels, which has been studied extensively [1,57,58]. It is generally acknowledged to be a two-step process of initial creation of small macromolecular aggregates and subsequent further aggregation of these molecular clusters.…”
Section: Network Formation Induced By Trivalent Star-like Tam Countermentioning
confidence: 99%
“…(ii) PROTOHYDRA CAULLERYI Dawydoff, 1930. Description in Dawydoff, 1930. Distribution. -Goas t of Indo -China.…”
Section: Summaries Of Descriptions Of Known Speciesmentioning
confidence: 99%